Property Rights and Gender Bias: Evidence from Land Reform in West Bengal - Sonia R. Bhalotra; Abhishek Chakravarty; Dilip Mookherjee; Francisco J. Pino (Institute for the Study of Labor (IZA), 2016)
While land reforms are typically pursued in order to raise productivity and reduce inequality across households, an unintended consequence may be increased within-household gender inequality. We analyse a tenancy registration programme in West Bengal, and find that it increased child survival and reduced fertility. However, we also find that it intensified son preference in families without a first-born son to inherit the land title. These families exhibit no reduction in fertility, an increase in the probability that a subsequent birth is male, and a substantial increase in the survival advantage of subsequent sons over daughters.
Keywords: I14; I24; J71; O15; 330; land reform; property rights; gender; infant mortality; sex ratio; fertility